Analisis daya dukung daya tampung lingkungan hidup dalam pengelolaan KPHP Kampar Kiri Kabupaten Kampar Provinsi Riau - M. Imran Sinaga; Thamrin Thamrin; Yusni Ikhwan Siregar (Pelantar Press, 2020)
With the development of the concept of utilizing natural resources with a supporting approach and environmental capacity, knowledge of the performance of ecosystem services is needed in planning the management of the Kampar Kir Production Forest Management Unit to ensure the sustainability of ecosystems that produce various ecosystem services needed for human life. This study aims to determine the condition of the carrying capacity and the carrying capacity of the environment in the Kampar Kiri forest management unit and the management block model that is formulated with an ecosystem services approach. This research belongs to naturalistic / qualitative research and the researcher does not treat it with analytical techniques using ArcGIS software. The research was conducted from July to December 2019. The results showed that the condition of the carrying capacity and carrying capacity of the forest area in KPH Kampar Kiri currently provides services for several types of ecosystem services which are considered as services that are relevant to the function of forest areas. Modeling of management blocks with the consideration of the Ecosystem Services approach provides a reference for 2 (two) types of management blocks in primary forests and 5 (five) types of management blocks in production forests. The area of each management block that is structured using an ecosystem services approach gives a different area variation from the existing blocks that are prepared using a natural resource grouping approach.